Peran Pemerintah dan Pemangku Kepentingan dalam Penanganan Stunting di Desa Loktuan, Bontang Utara - Sunyk Widiarsih; Kus Indarto; Saipul Saipul (Nakhoda: Jurnal Ilmu Pemerintahan, 2026)
This study analyzes the role of government and stakeholders in addressing stunting in Loktuan Village, North Bontang, through the lens of collaborative governance. The research highlights that the persistent prevalence of stunting is not solely a consequence of limited resources or program absence but stems from weak orchestration capacity, fragmented coordination, and the absence of integrated stakeholder collaboration. Using a qualitative research method with an interpretive approach, data were collected through in-depth interviews, observations, and document analysis involving local government officials, community health workers, and social actors. The findings reveal that although multi-sectoral programs exist, their implementation remains sectoral and disconnected due to a lack of shared accountability and interdependence among actors. Strengthening the government’s steering capacity, improving institutional coordination, and fostering continuous stakeholder collaboration are essential to transform fragmented efforts into an integrated governance system capable of achieving sustainable reductions in stunting.